Determining the relationships between climatic elements and thermal comfort and tourism activities using the tourism climate index for urban planning: a case study of Izmir Province - Adiguzel, Fatih; Bozdogan Sert, Elif; Dinc, Yucel; Cetin, Mehmet; Gungor, Senay; Yuka, Pakize; Sertkaya Dogan, Ozlem; Kaya, Efdal; Karakaya, Kayhan; Vural, Ercan (Springer Science and Business Media LLC, 2021)
The tourism climate index of local and international tourists, especially in summer, is determined using the thermal comfort relationship in the province of Izmir. The aim is to reveal the most suitable time and the most suitable area for tourism activities in İzmir Province. The temperature (maximum, minimum, and average) of 1960–2019, the relative humidity (minimum and average) from 39 meteorology stations, the precipitation (total and average), the sunshine duration (total), and the wind speed (average) data were studied and evaluated. The data obtained were arranged and transferred to the GIS (geographic information systems) environment. The inverse weighted average method—one of the interpolation methods—was used to estimate unknown points with the help of known points in the study area. The tourism climate index was used to determine the climatic comfort conditions of the province in terms of tourism to assess the effect of the climatic conditions on tourism. The tourism-based climatic comfort map of İzmir Province, which was obtained by using the average temperature, relative humidity, total rainfall, and wind data, was presented in 7 categories: unfavorable, marginal, acceptable, good, very good, excellent, and ideal. The variety of tourism activities that could be done in these months also increased the importance of this period. The results obtained in this study are important in terms of developing the tourism strategy of İzmir Province. Making tourism-based climatic comfort conditions for all provinces that are important in terms of tourism will make a significant contribution to the tourism strategy of our country.
Keywords: Precipitation (climatology); Turkey; Political Instability; Snow Making; Relative humidity; Political instability; Air temperature; Tourism; Climate conditions; Skis; Impact; Skiing; Urban planning; Information; Izmir; Wind velocity; Meteorology & Atmospheric Sciences; Urban climate; Social Sciences - Hospitality, Leisure, Sport & Tourism - Tourism; Weather; 13. Climate action; 11. Sustainability